X Provincial Scientific Event on the Ministry of the Interior Medical Services in Santiago de Cuba - Yuri Alvarez Magdariaga; Haydée Revilla Arias (Centro Provincial de Información de Ciencias Médicas, 2017)
On May 25th and 26th of this year, the X Provincial Scientific Event of the Ministry of  Interior Medical Services was carried out in Santiago de Cuba, under the sponsoring of the Comprehensive General Medicine Society Provincial Chapter, and with the main objective of fomenting the exchange of experiences, the dialogue and the scientific communication among its participants.  One hundred and eighteen delegates attended the event, among them, specialist and resident doctors of several branches, as well as stomatologists, nurses, psychologists and other health professionals who work at present in the medical services of this Ministry through the whole territory from Santiago.